2021
DOI: 10.1002/aic.17210
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic models for real‐time monitoring of cell culture processes using spatiotemporal just‐in‐time Gaussian processes

Abstract: Spectroscopic methods play an instrumental role in the implementation of the U.S. Food and Drug Administration outlined process analytical technology for biopharmaceutical manufacturing. Industrial spectroscopic calibration models are typically developed in an offline setting using traditional methods, such as partial least squares and principal component regression. Apart from the limiting performances of these conventional models under time‐varying operating conditions, these methods require access to extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The implemented kernel function which is a combination of the linear and the RBF kernel has previously been shown to be a viable combination for chemometric purposes in Chen et al (2007). In other cases, the RBF kernel alone was used for GPR models using near‐infrared and Raman spectroscopy data (Chen et al, 2007; Cui & Fearn, 2017; Tulsyan et al, 2021). In general, the authors consider the usage of covariance kernels beneficial to model the nonlinear observed spectral shift and baseline drift of the absorbance spectra compared with the linear subspace projections the PLSR models are based upon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The implemented kernel function which is a combination of the linear and the RBF kernel has previously been shown to be a viable combination for chemometric purposes in Chen et al (2007). In other cases, the RBF kernel alone was used for GPR models using near‐infrared and Raman spectroscopy data (Chen et al, 2007; Cui & Fearn, 2017; Tulsyan et al, 2021). In general, the authors consider the usage of covariance kernels beneficial to model the nonlinear observed spectral shift and baseline drift of the absorbance spectra compared with the linear subspace projections the PLSR models are based upon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another drawback of the implemented EKF is the steady-state constraints, that is, the experimentally derived cysteine distribution assumed for all batches, which make the EKF rather stiff towards the end of the reaction. This is a known problem of the EKF (Tulsyan et al, 2021) when dealing with only a few states being available for measurement as well as for nonlinear models. In theory, this problem could be circumvented with other more flexible state estimation algorithms, such as particle filters as implemented in Golabgir and Herwig (2016) and Stelzer et al (2017) or unconstrained Kalman filter algorithms as used in Kolås et al (2009) and Simutis and Lübbert (2017) which were beyond the scope of this study.…”
Section: Soft-sensor Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, there are many works where data‐driven cell culture process models are employed for monitoring and control purposes (Kiran & Jana, 2009; Tulsyan et al, 2021); however, the choice of model has a considerable impact on the accuracy and reliability of the control policy. Linear models normally have the simplest structure for representing the processes; however, nonlinear models such as neural networks (NN) and Gaussian process (GP) provide more accuracy.…”
Section: Introductionmentioning
confidence: 99%